SHILLONG SMART CITY: CHALLENGES AND OPPORTUNITIES - Das, Tapan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Urbanization is a symbol of modern civilization, development and technological power-house. No society can remain aloof from the process of urbanization and its consequent effects. However, given the technological advancement and industrial expansion, level of urbanization varies significantly from country to country. It is perhaps, rightly said that creators made the village and man created the city. It is the city that pulls people like a giant magnet from all walks of life to meet the demands of city life and exchanges its benefits and burdens. It is the city that attracts continuously people to come and engage in diverse fields of activity and in the production process of goods and services.